O Planejamento da drenagem urbana de Belém (PA): uma perspectiva sistêmica multinível - ELMESCANY, Raquel Serruya (Universidade Federal do Pará, 2024)
Belém, capital of Pará, metropolis of the Amazon, suffers from constant flooding and inundation. Thus, it is natural to ask what measures the government has planned over the years to deal with the problem, but several administrative instances do urban planning, from different perspectives. Therefore, the question arises: is there cohesion in the decisions and communications between the subsystems that intervene in the planning of urban drainage in Belém (PA), in a systemic and multilevel perspective? To answer, the Theory of Self Referential Systems was used, working on the theoretical categories of decision, communication and self-reference, in a multilevel perspective, observing the planning elaborated between the different administrative spheres that plan interventions related to drainage (Union, State, Metropolitan Region and Municipality), in three observational approaches: territorial, sectoral and budgetary decisions. Thus, the theory of social systems and a general overview of the rationalities applicable to urban planning were exposed, raising a theoretical proposal, which understands planning as a function of the political-administrative system, to be exercised by subsystems that, through planning decisions, can articulate themselves via governance and seek self-reference, via dynamic cohesion of their instruments. in the pursuit of common goals. An applied heuristic observation methodology was constructed, with the use of three data collection techniques: bibliographic research, documentary research and interviews; and three analysis techniques: narrative review, content analysis, and concomitant triangulation. The results were structured taking into consideration the administrative levels, additionally analyzing the organized technical sector and social movements linked to urban drainage. It was concluded that the drainage planning system of Belém is structured in practically isolated levels, with little communication between them, with the only communication commonly understood is the National Basic Sanitation Plan, although pending review and not fully observed by management. Pending issues such as the revision and publication of the State Basic Sanitation Plan, revision of the Municipal Master Plan, revision or observance of the Municipal Basic Sanitation Plan and the lack of an Integrated Urban Development Plan are configured as gaps in the drainage planning of Belém, lacking decisions, impairing the reach of communications. Thus, it is concluded that there is no cohesion in a multilevel perspective, as it comes up against, to a large extent, the lack of planning itself.